Overrepresentation of missense mutations in mild hemophilia A patients from Belgium: founder effect or independent occurrence?. Issue 6 (June 2015) - Lannoy, N.; Lambert, C.; Vikkula, M.; Hermans, C.
Abstract: Roughly 40% of observed mutations responsible for hemophilia A (HA) are novel and present in either a single family or a limited number of unrelated families. During routine diagnostic analysis of 73 unrelated Belgian patients with mild HA, 4 out of 43 different mutations (p.Ser2030Asn, p.Arg2178Cys, p.Arg2178His, and p.Pro2311His) were detected in more than one family, representing 35% of total identified mutations. To discriminate between an independent recurrence or a founder effect, an analysis of intra- and -extragenic single nucleotide polymorphisms (SNPs) and short tandem repeats (STRs) flanking the F8 gene was conducted. SNP haplotype and microsatellite analysis revealed strong evidence that p.Ser2030Asn and p.Pro2311His mutations were probably associated with a founder effect. The two other mutations localized in an F8 cytosine-phosphate-guanine (CpG) site likely resulted from recurrent de novo events. This study suggests that missense mutations producing C-to-T or G-to-A substitutions in CpG dinucleotide can occur de novo with more repetition than other causal substitutions that do not affect the CpG site. Analysis of F8 database implied that CpG sites throughout the F8 gene are not all mutated with the same frequency. Causes are still unknown and remain to be identified. Graphical Abstract: Highlights: Specific genetic mutations are more prevalent in some families with mild haemophilia A A causal independent de novo occurrence or a founder effect could be implicated. Missense mutations in CpG sites most likely result from recurrent de novo events